Long term results of postoperative Intensity-Modulated Radiation Therapy (IMRT) in the treatment of Squamous Cell Carcinoma (SCC) located in the oropharynx or oral cavity. Issue 1 (December 2015) - Hoffmann, M.; Saleh-Ebrahimi, L.; Zwicker, F.; Haering, P.; Schwahofer, A.; Debus, J.; Huber, P.E.; Roeder, F.
Abstract Background To report our long-term results with postoperative intensity-modulated radiation therapy (IMRT) in patients suffering from squamous-cell carcinoma (SCC) of the oral cavity or oropharynx. Methods Seventy five patients were retrospectively analyzed. Median age was 58 years and 84 % were male. 76 % of the primaries were located in the oropharynx. Surgery resulted in negative margins (R0) in 64 % of the patients while 36 % suffered from positive margins (R1). Postoperative stages were as follows: stage1:4 %, stage2:9 %, stage3:17 %, stage4a:69 % with positive nodes in 84 %. Perineural invasion (Pn+) and extracapsular extension (ECE) were present in 7 % and 29 %, respectively. All patients received IMRT using the step -and-shoot approach with a simultaneously integrated boost (SIB) in 84 %. Concurrent systemic therapy was applied to 53 patients, mainly cisplatin weekly. Results Median follow-up was 55 months (5–150). 13 patients showed locoregional failures (4 isolated local, 4 isolated neck, 5 combined) transferring into 5-year-LRC rates of 85 %. Number of positive lymph nodes (n  > 2) and presence of ECE were significantly associated with decreased LRC in univariate analysis, but only the number of nodes remained significant in multivariate analysis. Overall treatment failures occurred in 20 patients (9 locoregional only, 7 distant only, 4 combined), transferring into 3-and 5-year-FFTF rates of 77 % and 75 %, respectively. The 3-and 5-year-OS rates were 80 % and 72 %, respectively. High clinical stage, high N stage, number of positive nodes (n  > 2), ECE and Pn1 were significantly associated with worse FFTF and OS in univariate analysis, but only number of nodes remained significant for FFTF in multivariate analysis. Maximum acute toxicity was grade 3 in 64 % and grade 4 in 1 %, mainly hematological or mucositis/dysphagia. Maximum late toxicity was grade 3 in 23 % of the patients, mainly long-term tube feeding dependency. Conclusion Postoperative IMRT achieved excellent LRC and good OS with acceptable acute and low late toxicity rates. The number of positive nodes (n  > 2) was a strong prognostic factor for all endpoints in univariate and the only significant factor for LRC and FFTF in multivariate analysis. Patients with feeding tubes due to postoperative complications had an increased risk for long-term feeding tube dependency.